Hyperkähler Manifolds of Curves in Twistor Spaces - Bielawski, R. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
We discuss hypercomplex and hyperkähler structures obtained from higher degree curves in complex spaces fibring over P¹.